The Effect of Good Industrial Relations on Company Sustainable and Working Conditions Mediated by Collective Labor Agreement at PT X - Yusnaini, Yusnaini; Gunawan, Yakub; Tyas, Ari Anggarani Winadi Prasetyoning (Badan Pengembangan Sumber Daya Manusia Provinsi DKI Jakarta, 2025)
The legal relationship between employees and employers is essentially fair, despite differences in socio-economic status. However, in practice, labor relations often experience disharmony due to violations of collective labor agreement provisions. This study aims to analyze the legal standing of collective labor agreements in resolving industrial relations disputes between workers and employers. The research method employs a normative approach by analyzing legislation and relevant court decisions. The findings reveal that collective labor agreements possess binding legal force once registered with the industrial relations court and can serve as a legal basis in labor dispute resolution. The novelty of this study lies in emphasizing the position of collective labor agreements as an independent legal source, rather than merely a supplement to individual employment contracts. Furthermore, this study highlights the limited authority of industrial relations courts to annul such agreements—an issue rarely explored in previous studies. Thus, a thorough understanding of the legal power and limitations of collective agreements is crucial in building a just and sustainable industrial relations system.